penelitian Water Pollution Index and Microplastic Ecological Risk in The North Coastal Area of Situbondo - Arisda Maryama Santikanuri; Riyanto Haribowo; Sri Wahyuni (Jurnal Penelitian Pendidikan IPA, 2025)
Microplastic pollution in rivers can harm ecosystems and water quality. This study aims to assess water quality and the ecological risk of microplastics in 15 locations in the North Coastal Area of Situbondo, which include rivers and estuaries. Water samples were analyzed based on water quality parameters, such as pH, TDS, ammonia, salinity, turbidity, DO, and BOD. Microplastics were identified using binocular microscopes and FTIR, with characteristics (size, shape, color) recorded. The Water Pollution Index (IP) showed a mild level of pollution with values ranging from 1.322 to 3.897, where IP values 1-3 are considered "mildly polluted." Ecological risk analysis using the Pollution Load Index (PLI), Polymer Hazard Index (PHI), and Potential Ecological Risk Index (PERI) showed that industrial and residential areas had a higher risk of pollution. A significant correlation was found between microplastic color and water quality parameters based on CCA analysis. The results of this study indicate that despite moderate water quality, microplastics pose significant ecological risks, especially in areas with high human activity, emphasizing the need for better environmental management